HUBUNGAN STRUKTURAL KUALITAS LAYANAN, KUALITAS PRODUK, KEPUASAN PELANGGAN, DAN NIAT ULANG BERKUNJUNG KE PANTAI LONG MALANG DI SAMPANG - Pribanus Wantara; Muhammad Tambrin (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2021)
The purpose of this study was to examine the structural relationship between service quality, product quality, customer satisfaction, and re-visit intention. This research was conducted in the conditions of the Covid 19 pandemic and was carried out at a coastal tourist destination in Sampang Regency, Madura. Respondents in this study were 187 local tourists who were willing to complete this research. Analysis of Structural Equation Modeling (SEM) is used to analyze relationships. The results showed that service quality had a significant influence to tourist satisfaction, but the product quality did not have a significant effect on tourist satisfaction, and satisfaction have a significant effect on re-visit intention to tourist destinations in Long Malang beach of the Sampang Regency, Madura.